DEVELOPMENT STRATEGIES OF MICRO BUSINESS IN MAJALENGKA REGENCY - Ellen Rusliati; Mulyaningrum Mulyaningrum; Mujibah Achyar Sufyani (Faculty of Economics and Business, University of Pasundan, 2018)
The purpose of this study was to examine the development of micro business potential to utilize aerocity opportunities in Majalengka Regency that would change the livelihood and culture of the community. The local potential in Majalengka were agriculture and natural resource-based tourism. Processing of local raw materials into products that fit the needs of the community would be able to increase the income of the population. The research method used was descriptive qualitative. The results showed the right strategy was market penetration and new product development. Efforts to be taken to support the strategy included (1) Improving the quality of human resources in services and trade, (2) Innovation of new local based products, (3) Promotion of information technology utilization, (4) Increasing tourism infrastructure involving micro businessmen, (5) Business assistance, market survey, and management training involve Higher Education, (6) BUM Desa facilitations in machinery, storage, capital development, product marketing, (8) Producing products according to agricultural commodities.